KAJIAN PEMANFAATAN TEPUNG LABU KUNING (Cucurbita moschata Durch) DAN TEPUNG TEMPE DALAM PEMBUATAN KUKIS - Tambunan, Krisno; Ali, Akhyar; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research was to acquire best cookies which has high nutrition content from pumpkin flour and tempe flour and meet quality standard of cookies (SNI 01-2973-1992.This research used Complete Randomized Design (CRD) with four treatments and four replications. The treatments were P1 (65% pumpkin flour, 5% tempe flour), P2 (60% pumpkin flour, 10% tempe flour), P3 (55% pumpkin flour, 15% tempe flour) and P4 (50% pumpkin flour, 20% tempe flour). Data were analized using ANOVA and DNMRT at 5% level. The result showed that cookies from different pumpkin flour and tempe flour gave the significant effect to the moisture content, ash content, protein content, β-caroten content, valuation of description organoleptic and valuation of hedonic organoleptic to the colour, flavor, taste, total value, but non significant to texture in hedonic value and organoleptic assessment to the level of children like of cookies. The best cookies in this research is P3 with has 4,54% moisture content, 1,89% ash content, 10,71% protein content and 9,31% β-caroten content. Keyword: Cookies, pumpkin flour, tempe flour, β-caroten